Protective effects of long-term administration of Ziziphus jujuba fruit extract on cardiovascular responses in L-NAME hypertensive rats - Mohebbati, Reza (Avicenna J Phytomed, 2018)
OBJECTIVE: Ziziphus jujuba stimulates the release of nitric oxide (NO). Because NO is involved in cardiovascular regulations, in this study the effects of hydroalcoholic extract of Z. jujuba on cardiovascular responses in acute NG-nitro-L-arginine methyl ester (L-NAME) hypertensive rats were evaluated. MATERIALS AND METHODS: Rats were divided into 6 group (n=6): 1) saline, 2) L-NAME received (10mg/kg) intravenously, 3) sodium nitroprusside (SNP) (50µg/kg)+L-NAME group received SNP before L-NAME and 4-6) three groups of Z. jujuba (100, 200 and 400mg/kg) that treated for four weeks and on the 28(th) day, L-NAME was injected. Femoral artery and vein were cannulated for recording cardiovascular responses and drug injection, respectively. Systolic blood pressure (SBP), Mean arterial pressure (MAP) and heart rate (HR) were recorded continuously. Maximal changes (∆) of SBP, MAP and HR were calculated and compared to control and L-NAME groups. RESULTS: In L-NAME group, maximal ΔSBP (L-NAME: 44.15±4.0 mmHg vs control: 0.71±2.1 mmHg) and ΔMAP (L-NAME: 40.8±4.0 mmHg vs control: 0.57±1.6 mmHg) significantly increased (p<0.001 in both) but ∆HR was not significant as compared to control (p>0.05). All doses of Z. jujuba attenuated maximal ∆SBP and ∆MAP induced by L-NAME but only the lowest dose (100 mg/kg) had significant effects (ΔSBP: 20.36±5.6 mmHg vs L-NAME: 44.1±4.0 mmHg and ΔMAP: 20.8±4.5 mmHg vs L-NAME: 40.8±3.8 mmHg (p<0.05 to p<0.01)). The ∆HR at three doses was not significantly different from that of L-NAME group (p>0.05). CONCLUSION: Because long-term consumption of Z. jujuba extract, especially its lowest dose, attenuated cardiovascular responses induced by L-NAME, we suggest that Z. jujuba has potential beneficial effects in prevention of hypertension induced by NO deficiency.